Impacts of marine debris contamination in the mangrove ecosystem of the Ciénaga Grande de Santa Marta, Colombian Caribbean - Garcés-Ordóñez, Ostin (2019)
Marine debris generates negative impacts on marine ecosystems and human communities, which is why the solution to this relevant problem has been included in the Sustainable Development Goal No. 14. The aim of this study was to identify and assess the negative impacts of marine debris pollution on the mangrove ecosystem in the Ciénaga Grande de Santa Marta (CGSM), in the Colombian Caribbean. Impacts were identified through in situ observation (observed impacts) during field trips made in February 2018 and after reviewing the secondary information (potential impacts). Observed impacts were assessed based on the methodology proposed by Fernández-Vítora (2010), which takes into consideration the following criteria: intensity, extent, momentum, reversibility, recoverability, synergy and accumulation. In total, 10 impacts were identified in the field together with 11 potential impacts caused by marine litter in the CGSM mangroves. Presence, accumulation, and degradation of marine debris generate moderate, severe and critical impacts in the CGSM mangroves. Highlighted impacts due to their potential hazard to the ecosystem include microplastics accumulation, limitation of the propagules establishment, seedling growth, and physical changes in the soil. These results are useful for environmental authorities to take preventive measures and significant debris reduction actions and contribute to mangrove recovery and its environmental services.